Mechanical Regulation of Mitochondrial Dynamics and Function in a 3D-Engineered Liver Tumor Microenvironment - Frtús, Adam; Smolková, Barbora; Uzhytchak, Mariia; Lunova, Mariia; Jirsa, Milan; Petrenko, Yuriy; Dejneka, Alexandr; Lunov, Oleg (ACS biomaterials science & engineering, 2023)
It has become evident that physical stimuli of the cellular microenvironment transmit mechanical cues regulating key cellular functions, such as proliferation, migration, and malignant transformation. Accumulating evidence suggests that tumor cells face variable mechanical stimuli that may induce metabolic rewiring of tumor cells. However, the knowledge of how tumor cells adapt metabolism to external mechanical cues is still limited. We therefore designed soft 3D collagen scaffolds mimicking a pathological mechanical environment to decipher how liver tumor cells would adapt their metabolic activity to physical stimuli of the cellular microenvironment. Here, we report that the soft 3D microenvironment upregulates the glycolysis of HepG2 and Alexander cells. Both cell lines adapt their mitochondrial activity and function under growth in the soft 3D microenvironment. Cells grown in the soft 3D microenvironment exhibit marked mitochondrial depolarization, downregulation of mitochondrially encoded cytochrome c oxidase I, and slow proliferation rate in comparison with stiff monolayer cultures. Our data reveal the coupling of liver tumor glycolysis to mechanical cues. It is proposed here that soft 3D collagen scaffolds can serve as a useful model for future studies of mechanically regulated cellular functions of various liver (potentially other tissues as well) tumor cells.
Keywords: Humans; nádory jater; mitochondriální dynamika; Collagen; nádorové mikroprostředí; extracellular matrix; cytoskeleton; Mitochondrial Dynamics; Liver Neoplasms; mechanical forces; Tumor Microenvironment; kolagen; mitochondria; cancer; cell plasticity; engineered cell microenvironments; lidé